(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
This paper examines the potential transition from traditional budgeting to performance budgeting (PB) in Iraq, with a focus on the Government Program (GP). It explores the historical underpinnings of budgetary practices in Iraq, critiques the limitations of traditional budgeting, and delineates the potential of GP as a catalyst for the implementation of performance budgeting. The study utilizes a qualitative approach, analyzing policy documents and drawing parallels with global trends and empirical studies to assess the adaptability of performance budgeting in the Iraqi context. The findings suggest that GP embodies the foundational elements of performance budgeting. The study concludes with strategic recommendations for successful performance budgeting implementation in Iraq.